Temperature-responsive hairy particle-supported proline for direct asymmetric aldol reaction in water. Issue 108 (20th October 2015) - Li, Xinjuan; Yang, Beilei; Jia, Xianbin; Chen, Maoqin; Hu, Zhiguo
Abstract : In this paper, three kinds of hairy particles with different brush structures were prepared and evaluated as chiral catalysts in the direct asymmetric aldol reaction. Abstract : In this paper, three kinds of hairy particles with different brush structures were prepared and evaluated as chiral catalysts in the direct asymmetric aldol reaction. Compared to other hairy particles, hairy particle (1) grafted with amphiphilic copolymer chains showed a good conversion rate and an outstanding enantioselectivity in pure water. The copolymer brush on the surface of hairy particle (1) contained temperature responsive poly( N -isopropylacrylamide) which underwent a coil-to-globule transition at a lower critical solution temperature (LCST). The brush formed a hydrophobic nanocavity for the organic substrates, and it provided a suitable reaction microenvironment below and above the LCST of PNIPAM. The aldol reaction was promoted by the catalytic system and it showed stable reactivity from 25 °C to 50 °C. The significant advantages of the hairy particle supported catalytic system were that it was more efficient than the corresponding homogeneous polymer supported proline, and it can be recycled five times while maintaining activity and selectivity.